Legal protection for recipients of fidusians on fidusian guarantee released in the illegal logging crime action - Benny Yulianingsih; Sudiyana Sudiyana (Universitas Janabadra, 2020)
This thesis discusses the legal protection of third parties in the recovery of her belongings were confiscated in criminal acts. Third parties owners of goods in a criminal case are often less legal protection to regain possessions associated with crime. Not all laws that ordered the seizure and confiscation of the items related to the crime to protect third parties in acquiring possessions. That prompted this study to determine whether there is legal protection for fiduciary receiver in the recovery of her belongings were confiscated in criminal, how the legal ramifications if the judge in a criminal verdict does not return the goods belonging to third parties and how the criminal justice system is supposed to provide protection to fiduciary receiver. The results concluded that a third parties may be given legal protection and legal consequences by filing a civil lawsuit or intervene before the judge in the case decided that the decision not to take the property of a third parties, and the most important is the legal protection given by judges through decisions that visionary thinking ahead and have the moral courage to do the groundbreaking law, where a statutory provision that is contrary to the public interest, propriety, decency, and humanity, are the values that live in the community, the judge freely and authorized take a decision which is contrary to law article is concerned with a view to achieving truth and justice, so that decisions can be made permanent jurisprudence.